Execution time optimization analysis on multiple algorithms performance of moving object edge detection - Islam S.Z.; Islam S.Z.; Jidin R.; Mohd. Ali Mohd.A. (2023)
Computer vision and digital image processing comprises varieties of applications, where some of these used in image processing include convolution, edge detection as well as contrast enhancement. This paper analyzes execution time optimization analysis between Sobel and Canny image processing algorithms in terms of moving objects edge detection. Sobel and Canny edge detection algorithms have been described with pseudo code and detailed flow chart and implemented in C and MATLAB respectively on different platforms to evaluate performance and execution time for moving cars. It is shown that Sobel algorithm is very effective in case of moving multiple cars and blurs images with efficient execution time. Moreover, convolution operation of Canny takes 94-95% time of total execution time with thin and smooth but redundant edges. This also makes more robust of Sobel to detect moving cars edges. 2010 American Institute of Physics.